Studi Literatur: Peran Data Governance Dalam Meningkatkan Kualitas Data Untuk Pengambilan Keputusan Bisnis Di Era Digital - Jenia Silitonga; Mawar Agustina; Stela Tri Yuni Purba; Kasmawati (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
In the rapidly evolving digital business landscape, data has become a critical strategic asset for organizations. However, the increasing volume, variety, and velocity of data pose significant management challenges. Data governance provides a comprehensive framework of policies, standards, and roles to ensure that data is accurate, consistent, secure, and reliable throughout its lifecycle. Effective implementation enhances data quality across key dimensions accuracy, completeness, consistency, and timeliness directly strengthening data-driven business decisions. This approach supports evidence-based strategies, improves operational efficiency, ensures regulatory compliance, and fosters innovation, making data governance not merely a technical function but a strategic necessity for long-term success.